Counselling Portal (AskAkak.com) / Latifah Abd Latif - Latifah, Abd Latif (2003)
Throughout our lives we encounter many challenges like conflicts in relationship, life transaction, emotional crisis educational and career decisions. Sometimes the challenging are interested and sometimes there are frightening. And sometime we can be benefit from help and support as we strive to master them. Who is qualified to provide counseling portal? There is confusing issue for those who are seeking service. Today, there are a lot of portal offering service particularly in psychology from online counseling, e-counselor, motivation to behavioral analysis. The responses from user are overwhelming for those kind of online service. However, the current portal counseling system are mostly advertisement oriented. This is because, most of the website is playing role as a medium to advertise a particular physician business. Therefore, we develop this portal to help especially for the university students to discuss and solve their problems such as academic, career and relationship problems. Besides it is free, the students can share their problems among themselves in forum and chat room, which are provided in our portal. This portal ha two sections, which are user and administrator section. The user section allows users browse through all the services that the system provides like chat room, forum and etc. The administrator section provides an application for the administrator to update the counseling info in the database.